Impact of Leadership on Organizational Performance in the Private Banking Sector with Reference to Human Resource Outcomes - Vinita; Dr. Megha Bhatia (The Bioscan, 2025)
In the success of an organization, leadership plays a vital role. Depending on the circumstances, one leader may opt for a particular leadership style or a grouping of different styles. A leader’s day-to-day responsibilities may vary according to the nature of the organization. However, the job description of all leaders includes almost similar obligations. Organizational structures in the banking sector are getting gradually more dynamic. There is extra importance of headship all around in this sector. The bankers are now expected to be intelligent vendors and marketers as well. Skills of core banking will not support banks to spread their wings to the industrial and rural markets. Bank managers and leaders are supposed to foster selling skills among their employees to raise the branch's performance. In this study, the effects of leadership on the job satisfaction of employees of private banks and the organizational leadership behavior of different levels of managers and subordinates have been investigated. The hypotheses in the study have been tested using tools like linear regression analysis and ANOVA. The results of the analysis show a positive relationship between leadership and job satisfaction of employees in private banks.